Menggunakan Metode CAPM (Capital Asset Pricing Model) untuk Menentukan Kelompok Saham yang Efisien pada Perusahaan Sektor Farmasi di Masa Pandemi Covid-19 - Marxelino Aldymoro; Veny Anindya Puspitasari (The Indonesia Capital Market Institute, 2022)
The COVID-19 pandemic has undeniably affected various sectors in the Indonesian economy. One sector is the pharmaceutical sector. In this study, it is seen how the impact of the Covid 19 pandemic on stock efficiency in the securities company sub-sector in the pharmaceutical sector is seen. The method that will be used is the Capital Asset Pricing Model (CAPM). The purpose of this study was to determine the stocks of securities companies in the pharmaceutical sector that were efficient during the Covid 19 pandemic. The samples used in this study were 9 issuers of securities companies, namely DVLA, INAF, KAEF, KLBF, MERK, PEHA, PYFA, SIDO, and TSPC. Calculations were performed with Microsoft Excel with the CAPM formula. Thus, the calculation results will show that all research samples are efficient stocks or even though they have varying betas.